Common Evaluations of Disease Activity in Rheumatoid Arthritis Reach Discordant Classifications across Different Populations - Canhão, Helena; Rodrigues, Ana Maria; Gregório, Maria João; Dias, Sara S.; Melo Gomes, José António; Santos, Maria José; Faustino, Augusto; Costa, José António; Allaart, Cornelia; Gvozdenović, Emilia; van der Heijde, Desirée; Machado, Pedro; et al. (Frontiers in Medicine, 2018)
Objectives: The classification of disease activity states in Rheumatoid Arthritis (RA) can be achieved through disease activity indices, such as the Disease Activity Score in 28 joints erythrocyte sedimentation rate (DAS28-ESR), the Simplified Disease Activity Index (SDAI) and the Clinical Disease Activity Index (CDAI). Subjective measurements, such as patient reported outcomes have been incorporated into several of these indices alongside more objective assessments, such as increases in the ESR and C-reactive protein. Moreover, while they use similar criteria, different indices weight these criteria to different extents. Therefore, the classifications based on each evaluation may not always be the same. We aim to compare the performance of the three indices and their individual components in two different populations. Methods: Data from Dutch and Portuguese adherent centers were extracted from the METEOR database, a multinational collaboration on RA. We included a total of 24,605 visits from Dutch centers (from 5,870 patients) and 20,120 visits from Portuguese centers (from 3,185 patients). We compared the disease activity states as evaluated by the DAS28-ESR, CDAI, and SDAI across the two populations. In addition, we analyzed the individual components of each evaluation, including their respective contributions to the outcome, in each population. Results: We found significant differences in the disease activity states classified with the DAS28-ESR between the two populations. SDAI and CDAI had more congruous results. While the proportion of visits to Dutch and Portuguese centers that were classified as “in remission” was very similar between the CDAI and SDAI, the DAS28-ESR gave discordant results. Dutch patients had lower ESRs, which is more heavily weighted in the DAS28-ESR. In addition, even though the mean physicians’ global assessment values did not vary significantly for Dutch vs Portuguese physicians, we found that doctors at Portuguese centers overall scored the physician’s global assessment lower than Dutch physicians for patient visits classified by disease activity state. Conclusions: While the CDAI and SDAI assigned disease activity states that were largely similar, the DAS28-ESR was often discordant across the two populations. Moreover, we found that physicians, more than patients, evaluated disease activity differently among the Portuguese and Dutch populations.